Role of Teachers in Fostering Positive Communication Behavior among Elementary Students - Dafrizal Dafrizal; Silvia Novi Yanti; Oktri Permata Lani; Rahayu Ningsih; Herina Yanti; Putri Diana (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
The ever-evolving tide of globalization has a significant impact on children’s mindsets and behavior, potentially leading to a decline in moral values and social communication. This situation calls for teachers to play a key role as primary agents in fostering moral values and shaping positive communication behaviors at the elementary school level in Indonesia. This study aims to analyze the role of teachers in fostering positive communication among elementary school students through character development based on religious preaching and religious activities. The study employs a qualitative approach using a case study design. Data were collected through observation, in-depth interviews with Islamic Religious Education teachers and school principals, as well as documentation of instructional and extracurricular activities. Data analysis was conducted through the stages of data reduction, data presentation, and verification to obtain a comprehensive picture. The results of the study indicate that teachers play five dominant roles in fostering positive student communication, namely: i) teachers serve as the primary role models for polite and courteous behavior, ii) teachers act as mentors through preaching and guidance, iii) teachers integrate communication values into instruction, iv) teachers facilitate religious extracurricular activities, and v) teachers function as educators in educational discipline. The implications of this study emphasize that fostering positive communication is not only the responsibility of Islamic Religious Education teachers but also of all teachers, parents, and the community. Synergy between schools and families is necessary so that the cultivation of good character and positive communication can be consistently internalized, thereby fostering a culture of polite, empathetic, and civilized communication within the elementary school environment.